Gulaab gang - Nagpal, Amitosh 1984-; Chawla, Juhi 1967-; Dixit, Madhuri 1967- (2014)
Fearless Rajjo runs a martial academy for rural women. What happens when she faces ruthless politician Madam ji?
Orig.: Indien 2014